2017
DOI: 10.13005/ojc/330158
|View full text |Cite
|
Sign up to set email alerts
|

Novel Salt of Tinidazole with Improved Solubility and Antibacterial Activity

Abstract: The present study describes the preparation of novel salt of Tinidazole (TN) with p-Toluenesulfonic acid (PTSA) that display enhanced solubility and antibacterial activity in Bacillus. The salt was prepared by solvent-drop grinding and characterised by powdered X-Ray diffraction, thermal analysis, Fourier transformation infrared spectroscopy (FT-IR) and polarized microscopy. FT-IR data confirms Tinidazole salt with p-Toluenesulfonic acid (TN-PTSA). Powdered X-ray diffraction and thermal analysis data reveals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The 13 C CP/MAS spectra of TNZ-SA LAG (Figure 8g) and TNZ-SA CRYS-ETOH (Figure 8h) matched one another, indicating that the same cocrystalline phase was obtained by LAG and crystallization, in accordance with the PXRD data. The spectra exhibit, like those of the TNZ-PABA cocrystal (Figure 8e,f), noticeable upfield shifts for C-1 and the carboxylic carbon from the SA component (C-22).…”
Section: ■ Results and Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The 13 C CP/MAS spectra of TNZ-SA LAG (Figure 8g) and TNZ-SA CRYS-ETOH (Figure 8h) matched one another, indicating that the same cocrystalline phase was obtained by LAG and crystallization, in accordance with the PXRD data. The spectra exhibit, like those of the TNZ-PABA cocrystal (Figure 8e,f), noticeable upfield shifts for C-1 and the carboxylic carbon from the SA component (C-22).…”
Section: ■ Results and Discussionsupporting
confidence: 73%
“…In contrast, the DSC and TG curves of TNZ-SUC LAG (Figure S12) and TNZ-NA LAG (Figure S13) showed, in the 25−160 °C temperature range, single endotherms at 105.5 (T e ) and 102.6 °C (T e ) respectively, which were not accompanied by TG mass losses, and corresponded to melting processes as indicated by HSM. Taking into account that these endotherms occurred at temperatures below the observed DSC melting points (T e ) of TNZ and each coformer (SUC: 187.5 °C, and NA: 128.0 °C) and that PXRD, FTIR, and SS 13 C NMR indicated no interaction between the API and either coformer, these samples represented eutectic mixtures. Interestingly, the DSC curve of the TNZ-SUC PM (Figure S12) exhibited a single endotherm with a T e identical to that of the respective LAG sample, a result, which is also in accordance with Yamashita et al, 31 who observed only a single DSC endotherm, associated with eutectic melting, for binary physical mixtures incapable of cocrystal formation.…”
Section: A Tetramer Is Formed By C−h•••o Hydrogen Bonds With the C− H...mentioning
confidence: 99%
See 3 more Smart Citations